Evaluation of Open-Source E-Voting Systems Using Helios Voting in Public University Elections - Lima e Silva Junior, Cleovaldo José De; Vanderlei, Igor Medeiros; Araujo, Jean Carlos Teixeira De; Rocha, Rodrigo (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2022: Proceedings of the 28th Brazilian Symposium on Multimedia and the Web, 2022)
In the ideal model, universities are naturally constituted by democratic decisions involving voting from different collegiate bodies,commissions, sectors, and the general community. Following the trend of digital democracy, electronic voting tools have been significantly applied in Public Universities in recent years, accentuated by the Covid-19 pandemic. One of the characteristics of electronic voting software is that they have several layers of security and protocols that protect the integrity of a virtual election. This paper used the “Attack Tree” and “Risk Assessment” methods to propose and present a heuristic method of security assessment, which could serve as a model for future digital elections applied in Public Universities.